Production Obstacles and Marketing Patterns of Swamp Buffalo (Bubalus Bubalis Carabanensis) in West Kutai Regency - Nabil; Mayulu, Hamdi; Anindyasari, Dinar; Ibrahim (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The study aimed to determine the factors inhibiting production and marketing patterns of swamp buffaloes in Pulau Lanting Village, West Kutai Regency using survey methods and interview techniques. Data were collected using a questionnaire and analyzed using a descriptive approach for factors inhibiting buffalo production and a qualitative descriptive approach for marketing channel data analysis. Swamp buffalo farmers in Pulau Lanting village do not face significant barriers to swamp buffalo production in terms of feed requirements, grazing land provision, farmer capability, and swamp buffalo health, but require further investigation into the evaluation of feed ingredients to determine the nutritional adequacy of buffaloes so that swamp buffaloes can produce optimally, and additional new knowledge on the impact of inbreeding and diseases that can reduce swamp buffalo productivity. Recording applications are recommended to make it easier for farmers and/or health workers to find out the pedigree of swamp buffaloes, production history, maintenance management records, and health records to monitor health status in the context of efforts to develop swamp buffalo farming businesses